Model relative adaptive control (MRAC) for temperature regulation of herb drying system - Mohamad Jumain, Nur Hidayah (2021)
This project describe the development of temperature regulation for herb drying system. The most important factor for herb drying is temperature. The purposes of temperature are to maintain the quality of herb, prevent degradation of product and also to fast the dry process. The design of this project based on PID and MRAC. PID used as the benchmark on this project. For PID controller, P and PI controllers also build to do the comparison. There are two model of MRAC used which are standard MRAC and modified MRAC. Model reference adaptive control without integral (MRACWI) lastly achieve a better regulation temperature for herb drying system. Based on the results, it is shows that the MRACWI have better percentage improvement in term of settling time compared to PID and standard MRAC. For percentage of performance for MRACWI with 45℃, in terms of settling time it has 80.58% better than PID. For 50℃, it has 71.75% while when 55℃, it has 64.85% and 56.35% when 60℃. In conclusion, the biggest temperature, the lesser percentage of performance. It also shows that MRACWI has none overshoot. It provide that MRACWI is capable to provide robust and precise performance in controlling the temperature and produce better performance in terms of rise time, settling time and percentage overshoot as compared with PID controller and standard MRAC.